An Energy Efficient Multiuser Uplink Transmission Scheme in the Next Generation WLAN for Internet of Things - Woojin Ahn; Young Yong Kim; Ronny Yongho Kim (International Journal of Distributed Sensor Networks)
This paper proposes a novel and energy efficient Internet of Things (IoT) communication scheme for next generation Wireless Local Area Network (WLAN). There are a couple of crucial requirements among unique IoT requirements: a large number of communication devices must be supported, and they must have low power consumption. Since sensor-type IoT devices, which are expected to be one of the major types of IoT devices, normally generate uplink traffic rather than downlink traffic, an energy efficient multiuser uplink transmission scheme is a crucial feature of IoT communication. In the next generation WLAN, IEEE 802.11ax, Orthogonal Frequency Division Multiple Access (OFDMA) is adopted to support a greater number of devices. However, uplink OFDMA procedures that consider the unique IoT requirements have not been fully considered in the next generation WLANs. A random access-based WLAN uplink OFDMA transmission scheme is proposed in this paper, and analytical modeling of the proposed scheme is provided. The proposed random access-based WLAN uplink OFDMA transmission scheme is able to dynamically adjust the number of contending users by uniquely applying congestion status in a very simple and distributed manner. Our numerical analysis and extensive simulation corroborate the fact that the proposed scheme is able to support a greater number of IoT devices with less power consumption.